Rewards and incentives for the provision of human tissue for research. Issue 1 (10th May 2013) - Devaney, Sarah
Abstract : The Nuffield Council on Bioethics' 2011 report, Human Bodies: Donation for Medicine and Research, proposes a system for examining the ethical implications of different types of incentives for the provision of human tissue for use in medicine and research. The cornerstone of this system is the principle of altruism which, the Council recommends, should, where possible, remain the starting point for any such tissue provision. Using the Council's example of ova provision for research as an area in which altruism-based rewards might be departed from, this article argues that such a system has the potential to become inconsistent and unnecessarily complex. It suggests that the outcomes-focussed and motivations-focussed justifications the Council provides do not sit easily within the fast-paced and unpredictable area of biotechnology research. Further, it may undermine the focus on autonomy that is enshrined in the relevant legislation. This article suggests that a fair system for incentivising and rewarding the provision of human tissue in research should be developed, which focuses on elements of this role that are common to all tissue providers.